1) -6 3/4*5 1/3-4 1/3*3 3/13 2) (-2 1/6+1/4)*(-2 2/11)
3) 3 6/7*(-2 1/3)-8/9*(-1 7/8)
4) (-8 3/8+7 1/6)*(-2 14/29)

GAMERINO GAMERINO    1   02.12.2020 20:23    0

Ответы
VPVolkov03 VPVolkov03  01.01.2021 20:25

Пошаговое объяснение:

1) -6 3/4*5 1/3-4 1/3*3 3/13 =-49 1\3

-6 3\4*5 1\3=-27\4*16\3=-36

4 1\3*3 3\13=13\3*40\13=40\3=13 1\3

-36-13 1\3=-49 1\3

2) (-2 1/6+1/4)*(-2 2/11) =4 2\11

-2 1\6+1\4=-2 2\12+3\12=-1 11\12

-1 11\12*(-2 2\11)=-23\12*(-24\11)=46\11=4 2\11

3) 3 6/7*(-2 1/3)-8/9*(-1 7/8) =-7 1\3

3 6/7*(-2 1/3)=27\7*(-7\3)=-9

8/9*(-1 7/8) =8\9*(-15\8)=-15\9=-1 2\3

-9-(-1 2\3)=-9+1 2\3=-7 1\3

4) (-8 3/8+7 1/6)*(-2 14/29)=3

-8 3/8+7 1/6=-8 9\24+7 4\24=-1 5\24

-1 5\24*(-2 14/29)=-29\24*(-72\29)=3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика